Angry Black Woman: Debunking the Stereotype Through Black Women’s Lived Narratives - Green, Torrianah; Talpade, Medha (Journal of Student Research, 2023)
The purpose of this qualitative study was to explore and describe how black women cope with the angry black woman stereotype. Past research on black women’s anger indicated there is much psychological stress that comes with the perpetuation of the stereotype. Research questions are as followed: How do black women cope with the angry black woman narrative? What is the emerging story of the angry black women stereotype? Who are the players in this narrative? The research was conducted by way of the narrative approach to chronologically analyze the lived experiences of each participant. The sampling strategy was purposeful sampling through maximum variation. The data collection included interviews and observations. Validation strategies included member checking and rich thick descriptions. Biases were bracketed and reflexive which established dependability. Results revealed the following themes: Perpetuation, healing, and changing the narrative. Participant narratives of the 9 participants--3 black male, 3 young adult black women, and 3 older black women, indicated that ‘perpetuation of the stereotype’ was continued through the media and colorism; ‘healing’ starts with black women allowing other black women to simply exist ; and leading to ‘changing the narrative’ by not categorizing black women as angry. Implications of the results for future studies include creating a forum for only black women to participate in conversations that lead to the debunking of the stereotype. The results of this study can contribute to the field of social and experimental psychology and help initiate positive change for black women and the African American community.